Wing theory - Jones, Robert T. 1910-1999 (Princeton University Press, 1990)
Originator of many of the theories used in modern wing design, Robert T. Jones surveys the aerodynamics of wings from the early theories of lift to modern theoretical developments. This work covers the behavior of wings at both low and high speeds, including the range from very low Reynolds numbers to the determination of minimum drag at supersonic speed. Emphasizing analytical techniques, Wing Theory provides invaluable physical principles and insights for advanced students, professors, and aeronautical engineers, as well as for scientists involved in computational approaches to the subject. This book is based on over forty years of theoretical and practical work performed by the author and other leading researchers in the field of aerodynamics. Originally published in 1990. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.
Keywords: Airplanes -- Wings.; Aerofoils.; Aerodynamics.; elektronické knihy; electronic books